Elemental Diet Induces Histologic Response in Adult Eosinophilic Esophagitis - Peterson, Kathryn A; Byrne, Kathryn R; Vinson, Laura A; Ying, Jian; Boynton, Kathleen K; Fang, John C; Gleich, Gerald J; Adler, Douglas G; Clayton, Frederic (The American journal of gastroenterology, 2013)
Elemental diets have not been studied in adults with eosinophilic esophagitis (EoE). The goal of this trial was to assess the efficacy of an elemental diet in adults with EoE. A total of 18 adults with EoE were given an elemental diet for 4 weeks, or just 2 weeks if their response was complete. Symptoms and histologic findings, based on biweekly biopsies, were monitored. Six subjects were rebiopsied 2-7 days after resuming a normal diet. After therapy, esophageal tissue eosinophil content decreased from 54 to 10 per maximal high power field (P=0.0006). There was complete or nearly complete response (≤10 eosinophils) in 72% of subjects. Mast cell content, parabasal layer thickness, and endoscopic furrows and exudates also significantly decreased. Of the 29 qualified subjects, 11 (38%) failed to adhere to the diet. Several subjects had significant weight loss. Symptoms and endoscopic fixed strictures did not improve. After the subjects resumed a normal diet, the eosinophil content increased substantially in 3-7 days. While symptoms did not improve and dietary compliance was problematic, there was substantial histologic improvement after 4 weeks on the elemental diet. EoE in adults is substantially triggered by foods.